Психологічний аспект формування політичної свідомості, як складової політичної культури молоді - Пронза, І. І.; Пронза, И. И.; Pronza, І. (My University, 2010)
The main emphasis is on deﬁ ning the political culture and its components, in particular the political consciousness and the study of psychological factors. An analysis of existing conceptual approaches to deﬁ ning the content and the psychological components of political culture of the individual, to determine how to operationalize it.
Проноза І. І. Психологічний аспект формування політичної свідомості, як складової політичної культури молоді / І. І. Проноза // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 400-410.
Keywords: формування політичної свідомості; громадянська позиція молоді; соціальна активність молоді; політична культура особистості; формирование политического сознания молодежи; политическая культура молодежи; общественная позиция молодежи; социальная активность молодежи; the formation of political consciousness of youth; the political culture of youth; social position of young people; social activity of youth